PENERAPAN BETTER TEACHING AND LEARNING BERBASIS PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN BERPIKIR LOGIS DAN KEAKTIFAN SISWA (UPEJ Unnes Physics Education Journal, 2012)
The purpose of this study is to determine the increase in logical thinking and the level of students activity. This research is experimental and used control group pre-test post-test design. The population of this research is all class VIII student of SMP Negeri 1 Wanasari. The choose by purposive sampling technique. Two classes was taken as the samples: the class VIIIA as experiments class and the class VIIIB as control class. The data was collecting using analytical test and observation sheets. The results of the test gain for the control and experimental classes respectively obtained 29% and 50%. While the descriptive analysis of students activity class control to 62.43% and 68.18% for experiment classes. Then from the t-test obtained thitung (11.28) > ttable (1.68). While from hipotesys test average obtained thitung (6.585) > ttable (2.024). It can be concluded that the Better Teaching and Learning based cooperative was applied effective to improve logical thinking and students activity.